CPT1A mediates chemoresistance in human hypopharyngeal squamous cell carcinoma via ATG16L1-dependent cellular autophagy - Sun, Lianhui; Wang, Xing; Chen, Lixiao; Gao, Zheng; Xu, Songhui; Hu, Chen; Fan, Guangjian; Wang, Baoxin; Feng, Tingting; Wang, Wang; Ying, Xinjiang (Cell insight, 2023)
Hypopharyngeal squamous cell carcinoma (HSCC) is a highly aggressive malignancy that constitutes approximately 95% of all hypopharyngeal carcinomas, and it carries a poor prognosis. The primary factor influencing the efficacy of anti-cancer drugs for this type of carcinoma is chemoresistance. Carnitine palmitoyltransferase 1A (CPT1A) has been associated with tumor progression in various cancers, including breast, gastric, lung, and prostate cancer. The inhibition or depletion of CPT1A can lead to apoptosis, curbing cancer cell proliferation and chemoresistance. However, the role of CPT1A in HSCC is not yet fully understood. In this study, we discovered that CPT1A is highly expressed in HSCC and is associated with an advanced T-stage and a poor 5-year survival rate among patients. Furthermore, the overexpression of CPT1A contributes to HSCC chemoresistance. Mechanistically, CPT1A can interact with the autophagy-related protein ATG16L1 and stimulate the succinylation of ATG16L1, which in turn drives autophagosome formation and autophagy. We also found that treatment with 3-methyladenine (3-MA) can reduce cisplatin resistance in HSCC cells that overexpress CPT1A. Our findings also showed that a CPT1A inhibitor significantly enhances cisplatin sensitivity both in vitro and in vivo. This study is the first to suggest that CPT1A has a regulatory role in autophagy and is linked to poor prognosis in HSCC patients. It presents novel insights into the roles of CPT1A in tumorigenesis and proposes that CPT1A could be a potential therapeutic target for HSCC treatment. •The overexpression of CPT1A contributes to HSCC chemoresistance.•CPT1A interacts with and stimulate the succinylation of ATG16L1, which in turn drives autophagy.•The CPT1A inhibitor significantly enhances cisplatin sensitivity both in vitro and in vivo.